A systematic review and meta-analysis of randomized controlled trials comparing laparoscopic and open liver resection. Issue 10 (October 2021) - Haney, Caelán M.; Studier-Fischer, Alexander; Probst, Pascal; Fan, Carolyn; Müller, Philip C.; Golriz, Mohammad; Diener, Markus K.; Hackert, Thilo; Müller-Stich, Beat P.; Mehrabi, Arianeb; Nickel, Felix
Abstract: Background/purpose: The dissemination of laparoscopic liver resection (LLR) has been based on non-randomized studies and reviews of these. Aim of this study was to evaluate if the randomized evidence comparing LLR to open liver resection (OLR) supports these findings. Methods: A prospectively registered (reviewregistry866) systematic review and meta-analysis following Cochrane and PRISMA guidelines comparing LLR to OLR for benign and malignant diseases was performed via Medline, Web of Science, CENTRAL up to 31.12.2020. The main outcome was postoperative complications. Risk of bias was assessed with the Cochrane Risk of Bias tool 2.0, certainty of evidence was assessed using the GRADE approach. Results: The search yielded 2080 results. 13 RCTs assessing mostly minor liver resections with 1457 patients were included. There were reduced odds of experiencing any complication (Odds ratio (OR) [95% confidence interval (CI)]: 0·42 [0·30, 0·58]) and severe complications (OR[CI]: 0·51 [0·31, 0·84]) for patients undergoing LLR. LOS was shorter (Mean difference (MD) [CI]: −2·90 [-3·88, −1·92] days), blood loss was lower (MD: [CI]: −115·41 [-146·08, −84·75] ml), and functional recovery was better for LLR. All other outcomes showed no significant differences. Conclusions: LLR shows significant postoperative benefits. RCTs assessing long-term outcomes and major resections are needed.